China's Digital Silk Road in Africa and the Future of Internet Governance - Henry Tugendhat; Julia Voo (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2021)
The Digital Silk Road (DSR) is a Chinese policy initiative launched in 2015, yet six years later there is relatively little concrete information about what it has achieved so far. Henry Tugendhat and Julia Voo offer a preliminary analysis of what the DSR entails in Africa. Discover their findings, including how Chinese lending for technology projects in Africa was actually greater before the launch of the DSR than after.
Keywords: 330